ChemInform Abstract: A Safe and Scalable Synthesis of 2‐Hydroxy‐3‐alkoxypropionates by Epoxide Ring Opening. Issue 47 (November 2015) - Waring, Michael J.; Bennett, Stuart N. L.; Campbell, Leonie; Hallam, Stephen; Martin, Nathaniel G.; Tickner, Christopher
Abstract: Primary, secondary, and tertiary alcohol nucleophiles are employed in the magnesium triflate catalyzed ring‐opening of epoxide (I) to form the title products in moderate yields.